Analisis Determinan Cadangan Devisa Indonesia Tahun 1991-2020 - Wahyu Dian Santika; Ridho Dwiatmoko (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2022)
Foreign exchange reserves are the total value of international assets controlled by the government as the monetary authority. Foreign exchange reserves can be used to finance balance of payments imbalances or achieve monetary stabilization by intervening in the foreign exchange market. The position of Indonesia's foreign exchange reserves fluctuates greatly, there are many factors that can influence it, both from within and outside the country. This study will analyze the effect of the exchange rate, composite stock price index, world oil prices, net exports, and foreign debt on the position of Indonesia's foreign exchange reserves from 1991 to 2020 using Ordinary Least Square regression analysis. The regression results show that world oil prices, net exports, and foreign debt have a positive effect on foreign exchange reserves, while the exchange rate has a negative effect on foreign exchange reserves. Meanwhile, the composite stock price index was found to have no effect on the position of Indonesia's foreign exchange reserves.